Muhammad Abduh’s Perspective on Taqlid - Habib Widi Firdausi (Getpress Management Journals, 2025)
This study focuses on Muhammad Abduh’s thought on taqlid. The aim of the research is to examine and analyze the concept of taqlid as understood and criticized by Muhammad Abduh. The research problem addressed is: How is the concept of taqlid understood and critiqued within the framework of Muhammad Abduh’s rationalism? This study employs a qualitative library research method, which involves collecting data, information, and various sources available in the literature. The background of this research lies in the notion of taqlid, which refers to following the opinions of scholars without understanding the underlying evidence or arguments a subject of long-standing debate. On the one hand, taqlid is seen as a means to preserve the continuity of Islamic legal tradition (fiqh). On the other hand, it has been criticized for hindering intellectual progress and the exercise of ijtihad. The findings of this study reveal that Abduh’s criticism of taqlid was not aimed at abolishing the authority of scholars altogether. Rather, it sought to ensure that scholarly authority is grounded in scientific competence and contextual understanding. Accordingly, the key points of Muhammad Abduh’s critique include: excessive veneration of teachers, the proliferation of legal texts, the weakening of the Islamic state (daulah Islamiyah), the political authority of the sultan, the finality ascribed to mujtahid positions, the lack of attention to scientific knowledge, and the emergence of multiple legal schools (madhhab).